External networking, leadership style and innovation on organizational performance in Malaysian construction industry / Megat Zuhairy Megat Tajuddin - Megat Tajuddin, Megat Zuhairy (Institute of Graduate Studies, UiTM, 2016)
This study aims to investigate the factors influencing organizational performance through innovation in construction industry in Malaysia. External networking (EN) and leadership style (LS) were identified as the determinants for innovation (IN) and organizational performance (OP) in this study. EN links various parties in project implementation in the form of inter-organizational collaboration and appropriate LS adopted by managers are capable in bringing industry players to work together as a team, reducing the adversarial relationships among them for greater performance. While EN facilitates in establishing the channel for information and resource flows, managers influence their subordinates to pursue ambitious goals through innovative efforts. EN brings together a project team to innovate and leaders who encourage their subordinates to be innovative will effectively lead to greater performance. These indicatively explain the potential role of IN in mediating the relationship between the two determinants and OP. The Diffusion of Innovation Theory by Rogers (2003) is identified as the underpinning theory of this study. The nature of the study is based on hypothesis testing in a cross sectional setting…